Catalog of NIMS creep data sheets. Issue 1 (31st December 2019) - Sawada, Kota; Kimura, Kazuhiro; Abe, Fujio; Taniuchi, Yasushi; Sekido, Kaoru; Nojima, Takehiro; Ohba, Toshio; Kushima, Hideaki; Miyazaki, Hideko; Hongo, Hiromichi; Watanabe, Takashi
ABSTRACT: The background of the NIMS Creep Data Sheet Project, together with the preliminary study and facilities, material selection, and testing method, is summarized. The outcomes from the project are explained, focusing on the long-term creep strength of ferritic and austenitic heat-resistant steels. In some cases, the slope of the stress versus time-to-rupture curve in the long term differed from that in the short term in a manner that was markedly dependent on the type of material. Heat-to-heat variations in creep strength were recognized for ferritic and austenitic steels, even when the chemical compositions of the steels examined were within the range of specifications. The reasons for the heat-to-heat variations were differences in the chemical composition, in the amounts of minor elements, and in the grain size, among others. The existence of inherent creep strength was discovered in the very long term for ferritic heat-resistant steels. The amounts of minor solute elements affect the inherent creep strength, independently of precipitation strengthening or the dislocation structure. An inflection point was observed in the tertiary creep stage for a low-alloy steel and for austenitic stainless steels when precipitation occurred during creep. A region-splitting analysis method was proposed for long-term creep strength evaluation for high-chromium ferritic steels. This method was used to review the allowable stress of high-chromium ferritic steels in Japan. A metallographic atlas, time–temperature–precipitation diagram, and fracture-mode map were proposed for ferritic and austenitic steels on the basis of creep-ruptured specimens. Graphical Abstract: uf0001